2013
DOI: 10.1002/phy2.128
|View full text |Cite
|
Sign up to set email alerts
|

OVLT lesion decreases basal arterial pressure and the chronic hypertensive response to AngII in rats on a high-salt diet

Abstract: We have reported that lesion of the organum vasculosum of the lamina terminalis (OVLT) has no effect on basal levels of mean arterial pressure (MAP) but abolishes the hypertensive effects of angiotensin II (AngII) in rats consuming a normal-salt diet. These results suggest that the OVLT does not contribute to regulation of MAP under conditions of normal salt intake, but it is an important brain site for the hypertensive actions of AngII. The OVLT has been proposed as a major sodium sensor in the brain and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 40 publications
(87 reference statements)
4
31
2
Order By: Relevance
“…Among the possible outcomes, removal of peripheral chemoreflex may result in blood pressure increase, similar to previous results in malnourished rats (Penitente et al, 2007) or that increased pressor response could result from latent alterations corroborating with other factors to increase blood pressure levels late in life. Side studies, supporting the last hypothesis, showed that increased NaCl (2%) in the diet does not increase blood pressure by itself, but increase rostral ventrolateral medulla (RVLM) neurons excitability and lead to hypertension when combined with angiotensin II infusion (King et al, 2007;Stocker et al, 2010;Collister et al, 2013). Therefore, further studies are required to clarify the outcome of chemoreflex removal and interaction with baroreflex.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 85%
“…Among the possible outcomes, removal of peripheral chemoreflex may result in blood pressure increase, similar to previous results in malnourished rats (Penitente et al, 2007) or that increased pressor response could result from latent alterations corroborating with other factors to increase blood pressure levels late in life. Side studies, supporting the last hypothesis, showed that increased NaCl (2%) in the diet does not increase blood pressure by itself, but increase rostral ventrolateral medulla (RVLM) neurons excitability and lead to hypertension when combined with angiotensin II infusion (King et al, 2007;Stocker et al, 2010;Collister et al, 2013). Therefore, further studies are required to clarify the outcome of chemoreflex removal and interaction with baroreflex.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 85%
“…Limited data are available regarding the specific contribution of OVLT neurons (Collister et al . ). In regard to an Na + versus NaCl‐specific mechanism, Na + supplementation with non‐Cl − anions does not raise BP in these models (Kotchen et al .…”
Section: Discussionmentioning
confidence: 97%
“…The contribution of OVLT neurons to salt-sensitive hypertension is limited with the exception of one investigation in which OVLT lesion attenuated angiotensin II plus high salt hypertension. 32 …”
Section: Discussionmentioning
confidence: 99%